Penerapan Virtual Reality Tour Sebagai Media Promosi Perumahan Griya Pesona Cempaka Garut - Asep Deddy Supriatna; Siti Sarah Annashriyah (Institut Teknologi Garut, 2026)
Technological advancements have driven the emergence of innovations in property marketing strategies. Conventional methods, such as brochures and static images, are considered less capable of providing a comprehensive representation to prospective buyers. This study aims to design a Virtual Reality Tour based on Virtual Reality Photography (VRP) for Griya Pesona Cempaka Housing in Garut as an interactive promotional medium accessible via mobile devices and computers. The development was carried out using the Multimedia Development Life Cycle (MDLC) methodology, which consists of six main stages, from concept to distribution. Image capture was performed using an Insta360° X3 camera, while the virtual tour creation process utilized 3DVista software. Testing results using the black box testing method indicate that all functions operate as designed. The resulting Virtual Reality Tour is able to present detailed visual information and assist prospective buyers in gaining a clearer understanding of the environmental conditions and housing units. This study recommends periodic content updates to ensure the media remains engaging and relevant.